Pemasyarakatan Narapidana Narkotika dalam Mewujudkan Kesadaran Hukum - Rahantoknam, Wiska Watubtaran Rengmas; Pratama, Erwin Aditya (Diktum: Jurnal Ilmu Hukum, 2020)
Assimilation is part of the development process as well as the right of narcotics inmates inside the Penitentiary to mingle directly with the community outside the prison. In the application of assimilation often narcotics inmates commit irregularities that violate the rule of law, irregularities are carried out to obtain narcotics for addicts and for dealers to operate narcotics trafficking from inside prisons, this event indicates that the legal awareness of inmates undergoing the process of assimilation has not shown a success. The problems examined include First, how is the implementation of assimilation for narcotics inmates in Class II A Kendal Correctional Institution. Second, whether narcotics inmates are given special supervision while undergoing the process of assimilation. Third, how is the success rate of coaching narcotics inmates at the stage of assimilation in realizing legal awareness? This research uses the socio-legal approach method, data obtained through interviews and observations, then data processed descriptively analytically. The results showed that the implementation of assimilation of narcotics inmates was carried out in prisons as a preventive effort so as not to fall back on narcotics. Assimilation in prisons is carried out by involving people from outside prisons to carry out activities with narcotics inmates in various aspects such as education, sports, and the arts. Supervision is carried out strictly with certain restrictions by officers, inmate guardians, and also prison intelligence so that inmates do not feel intervened during the assimilation. The level of legal awareness shown by narcotics inmates at Kendal correctional institutions showed positive results in which they showed compliance with the rule of law in general and the rules of the potentiation and did not commit any violations in the process of assimilation.